A chemically fueled supramolecular glue for self-healing gels. Issue 38 (21st September 2022) - Rodon-Fores, Jennifer; Würbser, Michaela A.; Kretschmer, Martin; Rieß, Benedikt; Bergmann, Alexander M.; Lieleg, Oliver; Boekhoven, Job
Abstract : Chemically fueled supramolecular materials offer unique properties like the ability to self-heal, yet, mechanisms remain elusive. Here, we demonstrate that chemically fueled gels heal because of a molecular glue-based mechanism. Abstract : Chemically fueled supramolecular materials offer unique properties that include spatial and temporal control and even the ability to self-heal. Indeed, a few studies have demonstrated the ability to self-heal, however, the underlying mechanisms remain unclear. Here, we designed a peptide that forms a fibrillar network upon chemical fueling. We were surprised that the hydrogel could self-heal despite the lack of dynamics in the fiber assembly and disassembly. We explain this behavior by a mechanism that involves the chemically fueled peptide molecules that cannot self-assemble due to the lack of nucleation sites. When the fibers are perturbed, new nucleation sites form that help the assembly resulting in the healing of the damaged network. Furthermore, we generalized the behavior for other peptides. We refer to this non-assembling, chemically-fueled peptide as a molecular glue. In future work, we aim to explore whether this self-healing mechanism applies to more complex structures, narrowing the gap between biological and synthetic self-assemblies.